The influence of anemia on clinical outcomes in venous thromboembolism: Results from GARFIELD-VTE. Issue 203 (July 2021) - Goto, Shinya; Turpie, Alexander G.G.; Farjat, Alfredo E.; Weitz, Jeffrey I.; Haas, Sylvia; Ageno, Walter; Goldhaber, Samuel Z.; Angchaisuksiri, Pantep; Kayani, Gloria; MacCallum, Peter; Schellong, Sebastian; Bounameaux, Henri; et al.
Abstract: Introduction: Clinical characteristics and outcomes of venous thromboembolism (VTE) patients with concomitant anemia are unclear. This study compares baseline characteristics, treatment patterns, and 24-month outcomes in patients with and without anemia within GARFIELD-VTE. Materials and methods: GARFIELD-VTE (ClinicalTrials.gov : NCT02155491 ) is a global, prospective, non-interventional registry of real-world treatment practices. Of the 10, 679 patients enrolled in GARFIELD-VTE, 7698 were eligible for analysis. Primary outcomes were all-cause mortality, recurrent VTE, and major bleeding in VTE patients with or without concomitant anemia over 24-months after diagnosis. Event rates and 95% confidence intervals were estimated using Poisson regression. Adjusted hazard ratios were calculated using Cox proportional hazard models. Results: Distribution of VTE events in 2771 patients with anemia and 4927 without anemia was similar (deep-vein thrombosis alone: 61·1% vs. 55·9%, pulmonary embolism ± deep vein thrombosis: 38·9% vs. 44·0%, respectively). Patients with anemia were older (62.6 year vs. 58.9 years) than those without. At baseline, VTE risk factors that were more common in patients with anemia included hospitalization (22·0% vs. 6·8%), surgery (19·2% vs. 8·2%), cancer (20·1% vs. 5·6%) and acute medical illness (8·3% vs. 4·2%). Patients with anemia were more likely to receive parenteral anticoagulation therapy alone than those without anemia (26·6% vs. 11·7%) and less likely to receive a direct oral anticoagulant (38·5% vs. 53·5%). During 24-months of follow-up, patients with anemia had a higher risk (adjusted hazard ratio [95% confidence interval]) of all-cause mortality (1·84 [1·56–2·18]), major bleeding (2·83 [2·14–3·75]). Among anemia patients, the risk of all-cause mortality and major bleeding remained higher in patients with severe anemia than in those with mild/moderate anemia, all-cause mortality: HR 1·43 [95% CI: 1·21–1·77]; major bleeding: HR 2·08 [95% CI: 1·52–2·86]). Conclusions: VTE patients with concomitant anemia have a higher risk of adverse clinical outcomes compared with those without anemia. Further optimization of anticoagulation therapy for VTE patients with anemia is warranted. Highlights: GARFIELD-VTE compared 24-month outcomes in VTE patients with and without anemia VTE patients with anemia were less likely to received DOACs than those without anemia VTE patients with anemia had a higher risk of all-cause mortality and major bleeding Severe anemia was associated with a higher outcome risks than mild/moderate anemia